Thermogravimetric investigation of the oxygen content as a function of oxygen partial pressure in La 1.8 - Sr 0.2 - CuOy at 1173K - Caneiro, Alberto; Serafini, D.; Abriata, José Pablo; Andrade Gamboa, J. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Caneiro, Alberto Comisión Nacional de Energía Atómica; Argentina